Remote Teaching with the Cyber-Physical Mobility Lab. Issue 17 (2022) - Mokhtarian, Armin; Scheffe, Patrick; Kowalewski, Stefan; Alrifaee, Bassam
Abstract: Self-driving laboratories receive increasing acceptance as they are used in research and education. For research, they mainly serve as a platform on which algorithms can be tested under realistic conditions before getting deployed into the real world. In education, they can add value by creating a reference to reality as they offer an application for theoretical knowledge. In combination with the fact that practical work is well appreciated among students, such setup helps to motivate and thus enhance the learning experience. However, not every institution has the capabilities to create a self-driving lab on its own. Instead, open-source and remotely accessible laboratories, like our Cyber-Physical Mobility Lab (CPM Lab) can be used to engage with the domain of networked and autonomous vehicles. By means of two of our courses, we demonstrate the capabilities of the CPM Lab. These two courses can either be used as groundwork to develop own lectures in this domain, or used directly since the course materials are open-source.